(untitled) (European Journal of Marketing and Economics, 2021)
In their study, Relevance Lost: The Rise and Fall of Management Accounting, Johnson and Kaplan concluded that management accounting systems since the 1980s have failed to meet the new challenges of a changing environment. Among other things, because managerial accounting has been subordinated to the needs of financial accounting. Financial accounting cannot provide adequate information to management and does not support strategic decision making. The reason for this can be found in the operational logic of financial accounting. Financial accounting is past-oriented, it evaluates (economic) events in money, and thinks in the short term. Would all this mean that financial accounting data cannot be used to support long-term decisions? In our study, we point out the connection between financial accounting data assets and strategic decision support. Our research question focuses on how financial accounting data, including an invoice issued by a company, can be used in Balanced Scorecard perspectives. Based on the content of the Balanced Scorecard, we want to point out where and what kind of relationship can be observed between financial accounting data assets and the BSC. Through a case study, we will present the strategic goals as well as the indicators suitable for measuring the goals. These will be presented for all aspects of the Balanced Scorecard.